Transactional Leadership and Innovative Behavior as Factors Explaining Emotional Intelligence: A Mediating Effect - Noreña Chávez, Diego Alonso (2022)
This research aimed to determine the mediating effect of innovative behavior on the relationship between transactional leadership and emotional intelligence in a SARS-CoV-2 context. During this period, behavioral issues among and between employees have been modified in a way that transactional leadership and innovative behavior were considered differently as factors explaining emotional intelligence. This research gap gave room for additional research to re-define the hypothesis of an existing mediating effect between these issues. In fact, as the empirical part of the research has proven, there is evidence of a mediating effect on the relationship of these variables in the sample used. A random sample of 403 owners of textile companies from the Gamarra Commercial Emporium in the district of La Victoria in Lima, Peru, was used to test the existing model regarding the factors explaining emotional intelligence. Data were evaluated by partial least squares structural equation modeling (PLS-SEM). It was determined that innovative behavior has a total mediating effect on the relationship between transactional leadership and emotional intelligence and that 15.9% of the variance of the emotional intelligence variable is explained by the model. This study theoretically contributes to the literature and provides empirical evidence of the relationship between the variables included in the model. Likewise, the model of the variables generated is useful both for the academic and business worlds; yet it must be strengthened and improved by adding more variables. This research contributes to deepening the understanding of the relationship between emotional intelligence, transactional leadership, and innovative behavior in the textile field during the SARS-CoV-2 period.